A meta-analysis of measurement properties of the Western Ontario Meniscal Evaluation Tool (WOMET) - Krott, Nikolas Leon; Wild, Michael; Betsch, Marcel (Journal of Orthopaedic Surgery and Research, 2020)
Background: We provide a meta-analysis for clinicians and researchers regarding the psychometric properties of the WOMET as a patient-reported outcome measure (PROM) for patients with meniscal pathologies. Methods: A comprehensive literature search identified 6 eligible papers evaluating WOMET measurement properties in patients with different meniscal injuries and meniscal treatments following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The quality of the included studies was evaluated using the four-point Consensus-based Standard for the selection of health Measurement Instruments (COSMIN) Checklist for good measurement properties. The checklist was specifically developed for studies on health-related PROMs. Results: Our meta-analysis suggests that the WOMET can be used to evaluate patients with different meniscal injuries and meniscal treatments, especially acute or chronic meniscal injuries and traumatic or degenerative meniscal injuries treated operatively or conservatively. The WOMET shows satisfactory internal consistency, test-retest reliability, and construct validity. Due to limitations in both sample sizes and methodologies of the included studies, no conclusions can be drawn regarding the WOMET’s content validity, structure validity, cross-cultural validity, measurement error, or responsiveness. A further limitation of the studies included in this meta-analysis is the lack of cross-cultural validation, although recommended by the COSMIN Standards. Conclusions: The first meta-analysis on measurement properties of the WOMET demonstrates satisfactory internal consistency, test-retest reliability, and construct validity. Further studies are needed, focusing on the methodological deficiencies highlighted in this meta-analysis. To ensure that the WOMET adequately reflects the symptoms, functions, and quality of life of patients with meniscal tears based on COSMIN criteria, it is necessary to assess the structural validity and content validity of this PROM.
CRIS-Team Scopus Importer:2022-07-20
Keywords: COSMIN; Measurement properties; Meta-analysis; Patient-reported outcome measures; WOMET; Meniscal pathologies